Impacts of enemy-mediated effects and the additivity of interactions in an insect trophic system - Reigada, Carolina; Araujo, Sabrina Borges Lino; de Aguiar, Marcus Aloizio Martinez; Gião, Juliana Zibordi [UNESP]; Guimarães Jr., Paulo Roberto; Trinca, Luzia Aparecida [UNESP]; Godoy, Wesley Augusto Conde (Wiley, 2013)
In this study, we used data from both experiments and mathematical simulations to analyze the consequences of the interacting effects of intraguild predation (IGP), cannibalism and parasitism occurring in isolation and simultaneously in trophic interactions involving two blowfly species under shared parasitism. We conducted experiments to determine the short-term response of two blowfly species to these interactions with respect to their persistence. A mathematical model was employed to extend the results obtained from these experiments to the long-term consequences of these interactions for the persistence of the blowfly species. Our experimental results revealed that IGP attenuated the strength of the effects of cannibalism and parasitism between blowfly host species, increasing the probability of persistence of both populations. The simulations obtained from the mathematical model indicated that IGP is a key interaction for the long-term dynamics of this system. The presence of different species interacting in a tri-trophic system relaxed the severity of the effects of a particular interaction between two species, changing species abundances and promoting persistence through time. This pattern was related to indirect interactions with a third species, the parasitoid species included in this study. © 2012 The Society of Population Ecology and Springer Japan.
Keywords: Calliphoridae; Cannibalism; Host-parasitoid interaction; Intraguild predation; Population dynamics; Shared enemy; cannibalism; fly; host-parasitoid interaction; insect; intraguild predation; long-term change; numerical model; probability; trophic structure; Hexapoda